PENGGUNAAN KARTU MATEMATIKA DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR ALJABAR PESERTA DIDIK KELAS VII.1 MTSN 4 KOTA PADANG MELALUI TEAM GAME TOURNAMENT - DESMIARTI DESMIARTI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
The background of this research is that there are still many students who are not paying attention when the teacher explains the lesson, afraid to ask questions if they find difficulties about the material. The low learning motivation and student involvement greatly affect the smooth teaching and learning process, so that students' mathematics learning outcomes do not meet the Minimum Completeness Criteria (KKM). For this reason, a learning strategy is needed that makes students active in learning and improves student learning outcomes. One way to fulfill these expectations is to use math cards by applying the Team Game Tournament (TGT) learning strategy. The subjects of this class action research (PTK) were class VII.1 students of MTsN 4 Padang City for the 2021/2022 academic year, a total of 29 people. The results of the percentage of student activity obtained through the observation sheet showed that student activity significantly increased with the tournames between groups. And the percentage of student completeness increased from the learning outcomes of the first cycle, namely from 74.19% to 90.22% of the final learning outcomes test of the second cycle. Based on the results of the study, it can be concluded that the Learning Tournament Type learning strategy can increase the activity and learning outcomes of class VII.1 MTsN 4 Padang City. ABSTRAKPenelitian ini dilatarbelakangi masih banyaknya siswa yang kurang perhatian saat guru menerangkan pelajaran, takut bertanya jika menemukan kesulitan tentang materi. Masih rendahnya motivasi belajar dan keterlibatan siswa sangat mempengaruhi kelancaran proses belajar mengajar, sehingga hasil belajar matematika siswa belum memenuhi Kriteria Ketuntantasan Minimal (KKM). Untuk itu diperlukan strategi pembelajaran yang menjadikan siswa aktif dalam belajar serta meningkatkan hasil belajar siswa. Salah satu cara yang dapat memenuhi harapan tersebut adalah penggunaan kartu matematika dengan menerapan strategi belajar Team Game Turnamen (TGT). Subjek Penelitian tindakan kelas (PTK) ini adalah siswa kelas VII.1 MTsN 4 Kota Padang tahun pelajaran 2021/2022 yang berjumlah 29 orang. Hasil persentase aktivitas siswa diperoleh melalui lembar abservasi terlihat aktivitas siswa signifikan meningkatan dengan adanya tourname antar kelompok. Dan presentase ketuntasan siswa meningkat dari hasil belajar siklus I yaitu dari 74, 19% kepada 90,22% dari tes hasil belajar akhir siklus II. Berdasarkan hasil penelitian dapat disimpulkan bahwa strategi belajar Tipe Turnamen Belajar dapat meningkatkan aktivitas dan hasil belajar siswa kelas VII.1 MTsN 4 Kota Padang.